2005
DOI: 10.1159/000089002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Tetrahydrobiopterin Deficit in Schizophrenia

Abstract: Tetrahydrobiopterin (BH4) is a vital cofactor maintaining availability of the amine neurotransmitters [dopamine (DA), noradrenaline (NA), and serotonin (5-HT)], regulating the synthesis of nitric oxide (NO) by nitric oxide synthase (NOS), and stimulating and modulating the glutamatergic system (directly and indirectly). These BH4 properties and their potential relevance to schizophrenia led us to investigate the hypothesis of a study group (healthy controls, n = 37; schizophrenics, n = 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 155 publications
7
32
0
1
Order By: Relevance
“…Thus, both the lower values of neopterin and the Cit-Arg ratio and the observed association between these parameters found in bipolar affective disorders, indicate a reduced activity of BH4 and a decreased formation of NO in this group, in contrast to the group of major depressive disorders with melancholic features or a seasonal pattern. These findings are in agreement with those reported recently by Richardson et al [32] in a large sample of patients with schizophrenia and support the idea that bipolar affective disorder and schizophrenia share common pathophysiological patterns [33] .…”
Section: Discussionsupporting
confidence: 93%
“…Thus, both the lower values of neopterin and the Cit-Arg ratio and the observed association between these parameters found in bipolar affective disorders, indicate a reduced activity of BH4 and a decreased formation of NO in this group, in contrast to the group of major depressive disorders with melancholic features or a seasonal pattern. These findings are in agreement with those reported recently by Richardson et al [32] in a large sample of patients with schizophrenia and support the idea that bipolar affective disorder and schizophrenia share common pathophysiological patterns [33] .…”
Section: Discussionsupporting
confidence: 93%
“…Another study reported that total biopterin levels were only low in plasma and but not in urine of patients diagnosed with schizophrenia (59). In contrast, more recent studies found profound reductions in plasma total biopterin levels in schizophrenia and schizoaffective patients (by 34% and 25%, respectively) compared to normal controls (60,61). Meta-analysis studies for the International Database of BH4 Deficiencies found significant correlation between biopterin levels in plasma and CSF but failed to establish such a correlation between biopterin levels in urine and CSF of schizophrenia patients (60).…”
Section: Tetrahydrobiopterin In Schizophreniamentioning
confidence: 95%
“…Patient subjects did not have access to alcohol or drugs. Control and schizophrenic subject recruitment has been described previously [26]. Of note, for each normal control subject an interview was conducted and internal scale completed to determine no personal and/or family history for psychiatric, neurological, and medical conditions.…”
Section: Subjectsmentioning
confidence: 99%
“…At 6:30 a.m. on the morning of the evaluation, a blood sample was drawn from the antecubital vein using a needle and evacuated tube (fasting period of at least 8.5 h). A 4 ml plasma sample was then immediately processed via iodine oxidation under acid conditions, and stored at (-70°C, prior to total plasma biopterin assay, as we have previously described [26]. Plasma phenylalanine was determined as previously described [26], and was assayed because of its known role in the biosynthesis of BH 4 via the attenuation of BH 4 -mediated GTPCH inhibition [32][33][34][35].…”
Section: Plasma Collectionmentioning
confidence: 99%
See 1 more Smart Citation